Modification of 4-Fold and B-Pores in Bacterioferritin from Mycobacterium tuberculosis Reveals Their Role in Fe 2+ Entry and Oxidoreductase Activity - Parida, Akankshika; Mohanty, Abhinav; Raut, Rohit Kumar; Padhy, Ipsita; Behera, Rabindra K. (Inorganic chemistry, 2023)
The self-assembled ferritin nanocages, nature's solution to iron toxicity and its low solubility, scavenge free iron to synthesize hydrated ferric oxyhydroxide mineral inside their central cavity by protein-mediated ferroxidase and hydrolytic/nucleation reactions. These complex processes in ferritin commence with the rapid influx of Fe ions the inter-subunit contact points (i.e., pores/channels). Investigation of these pores as Fe uptake routes in ferritins remains a subject of intense research, in iron metabolism, toxicity, and bacterial pathogenesis, which are yet to be established in the bacterioferritin (BfrA) from ( ). The electrostatic properties of this protein indicate that the 4-fold and B-pores might serve as potential Fe entry routes. Therefore, in the current work, electrostatics at/along these pores was altered by site-directed mutagenesis to establish their role in Fe uptake/oxidation (ferroxidase activity) in BfrA. Despite forming self-assembled protein nanocompartment, these 4-fold and B-pore variants exhibited partial loss of ferroxidase activity and lower accumulation of transient species, which not only indicated their role in Fe entry but also suggested the existence of multiple pathways. Although the B-pore variants inhibited the rapid ferroxidase activity to a larger extent, they had minimal impact on their cage stability. The current work revealed the relative contribution of these pores toward rapid Fe uptake/oxidation and cage stability, possibly as consequences of their differential symmetry, number of modified residues (at each pore), and heme content. Therefore, these findings may help to understand the role of these pores in iron acquisition and proliferation under iron-limiting conditions to control its pathogenesis.